Rugby : more than just a game : a study of the cumulative effects of mild head injuries on high school rugby players - Giai-Coletti, Cristina (Rhodes University, Faculty of Humanities, Department of Psychology)
The present study comprises part of an ongoing research study investigating the effects 0 f cumulative mild head injuries 0 n Rugby Union p layers. The aim 0 f t he study was to ascertain whether there are neuropsychological effects of cumulative mild head injuries sustained during the rugby-playing careers of senior schoolboy rugby players. Participants were top-level rugby players from high schools in Grahamstown and Cape Town (n = 79) and non-contact sport controls of top-level field hockey players from the same schools (n = 58). Group mean comparisons across a battery of neuropsychological tests were carried out between the Total Rugby versus the Total Field Hockey group, and the Rugby Forwards versus the Rugby Backs group. Comparisons between Total Rugby versus Total Field Hockey revealed impaired performance by the rugby players on two tests of visuoperceptual tracking, namely Digit Symbol Substitution and Trail Making Test (Part A). For Rugby Forwards versus Rugby Backs, there were no consistent differences to support the expectation that forwards would perform worse than backs. Forwards performed more poorly than backs on WMS Associate Learning Subtest - Hard (Delayed Recall), whereas backs performed more poorly than forwards on Digits Backwards. This suggests that some individuals in the cohort were starting to exhibit verbal memory deficit, albeit not clearly in association with forward positional play. Overall, results of the present study provide tentative support for the hypothesis that school level rugby players are more susceptible to the effects of cumulative concussive and sub-concussive head injuries than are non-contact sport controls.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Head -- Wounds and injuries -- Complications; Rugby football injuries; Brain -- Concussion -- Complications; Neuropsychological tests